Effect of Photoperiod on Nutritional Quality of Muscle and Lipid Metabolism of Litopenaeus vannamei - Yingying Fang; Fan Fei; Fulu Guo; Chengliang Zhu; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Fishes, 2024)
Photoperiod serves as a significant environmental signal for organisms and plays a critical role in regulating their metabolic processes. This research aimed to investigate the lipid metabolism and nutritional quality of adults Litopenaeus vannamei (wet weight: 11.27 ± 0.73 g, body length: 12.45 ± 0.42 cm) under five photoperiods (0L:24D, 8L:16D, 12L:12D, 16L:8D, and 24L:0D) for 40 days in recirculating water systems (RASs). The 24L:0D group increased lipid metabolism, as indicated by increased lipid metabolism enzyme levels and related gene expression linked to lipogenesis. Additionally, shrimp in the 24L:0D exhibited the highest value of crude fat. The 0L:24D showed a significantly reduced content of crude fat compared with the 8L:16D and 12L:12D. In 24L:0D, the content of total essential amino acids (TEAAs), total hydrolyzed essential amino acids (THEAAs), and total non-essential amino acids (TNEAAs) increased significantly. Similarly, the content of polyunsaturated fatty acids (PUFAs) in 24L:0D was also higher than in other groups. Conversely, 0L:24D resulted in lower metabolic activity and a reduction in PUFA content. In conclusion, prolonging light could benefit shrimp cultivation. This study thoroughly examined the effects of varying photoperiods on muscle quality and lipid metabolism in L. vannamei, providing essential insights for the improvement of indoor aquaculture environments. Provision of light for 24 h improves production but has some adverse effects on animal welfare, so a 16 h light cycle is recommended.